Zagrożenia systemów informatycznych e-administracji – szkodliwe oprogramowanie i ataki: The risks of IT systems in e-administration – malicious software and attacks - Kowalczyk, Marcin (Management and Administration Journal, 2021)
The paper shows risks of IT systems: technical aspects of malicious software and attacks. In the Internet and a intranet. The article presents an overview of techniques and security recommendations for companies and offices for administration, databases and data processing.